Safety and Efficacy of Durvalumab (MEDI4736), an Anti–Programmed Cell Death Ligand-1 Immune Checkpoint Inhibitor, in Patients With Advanced Urothelial Bladder Cancer - Massard, Christophe (J Clin Oncol, 2016)
PURPOSE: To investigate the safety and efficacy of durvalumab, a human monoclonal antibody that binds programmed cell death ligand-1 (PD-L1), and the role of PD-L1 expression on clinical response in patients with advanced urothelial bladder cancer (UBC). METHODS: A phase 1/2 multicenter, open-label study is being conducted in patients with inoperable or metastatic solid tumors. We report here the results from the UBC expansion cohort. Durvalumab (MEDI4736, 10 mg/kg every 2 weeks) was administered intravenously for up to 12 months. The primary end point was safety, and objective response rate (ORR, confirmed) was a key secondary end point. An exploratory analysis of pretreatment tumor biopsies led to defining PD-L1–positive as ≥ 25% of tumor cells or tumor-infiltrating immune cells expressing membrane PD-L1. RESULTS: A total of 61 patients (40 PD-L1–positive, 21 PD-L1–negative), 93.4% of whom received one or more prior therapies for advanced disease, were treated (median duration of follow-up, 4.3 months). The most common treatment-related adverse events (AEs) of any grade were fatigue (13.1%), diarrhea (9.8%), and decreased appetite (8.2%). Grade 3 treatment-related AEs occurred in three patients (4.9%); there were no treatment-related grade 4 or 5 AEs. One treatment-related AE (acute kidney injury) resulted in treatment discontinuation. The ORR was 31.0% (95% CI, 17.6 to 47.1) in 42 response-evaluable patients, 46.4% (95% CI, 27.5 to 66.1) in the PD-L1–positive subgroup, and 0% (95% CI, 0.0 to 23.2) in the PD-L1–negative subgroup. Responses are ongoing in 12 of 13 responding patients, with median duration of response not yet reached (range, 4.1+ to 49.3+ weeks). CONCLUSION: Durvalumab demonstrated a manageable safety profile and evidence of meaningful clinical activity in PD-L1–positive patients with UBC, many of whom were heavily pretreated.